The Implementation of Simple Project-Based Learning Syntaxes to Improve Comprehension Elements in Teaching Speaking - M. Era azhari; Muhammad Husnu; Ahmad Yusri; Zahratul Fikni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Speaking is one of the English skills needed to obtain better achievement, and communication skills are needed when collaborating with one another. This research aims to know the implementation of simple Project-Based Learning (PJBL) syntaxes in improving comprehension elements in teaching. Speaking is the expected skill that is always promoted at school and university. This research is qualitative. The data collection used close-ended interviews. Data analysis was carried out by describing the results of the observation. However, the sample of this research took class VIII students of SMA 1 Sembalun as research participants. Importantly, the research showed that PJBL helped students comprehend the narrative text directly in front of the class. It is such a bonus that research PJBL also improves student vocabulary based on students’ answers. Many projects can be used in PJBL to improve students’ Comprehension, and Project-Based Learning (PJBL) can be used to help students improve their speaking. Keywords: Project-Based Learning, Comprehension, Speaking Skill.